(untitled) (Communications in Mathematical Research, 2021)
In this paper, we consider the decomposition of Zinbiel algebras with a special bilinear form which are called quadratic Zinbiel algebras. We obtain that the decomposition into irreducible ideals of a quadratic Zinbiel algebra is unique under an isometry.